Kajian Psikologis terhadap Pengaruh Pandangan Islam dalam Pembentukan Sikap dan Perilaku LGBT : Studi Kasus Pesta Seks 56 Gay di Jakarta Selatan - Nurhafidah, Leni; Nurfalah, Fadilah; Abdillah, Mochamad Ilham; Prabawa, Salvia Nasywa; Fajrussalam, Hisny (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
The LGBT (Lesbian, Gay, Bisexual, and Transgender) phenomenon has become a controversial global issue, including in Indonesia, where social and religious norms play a major role in shaping people's attitudes. Within the Islamic context, the LGBT community is regarded as being in opposition to human nature and the tenets of sharia law, leading to its frequent rejection. From a psychological perspective, individuals who identify as LGBT face mental distress, anxiety, and identity conflict due to social stigma. This research aims to analyze the influence of Islamic views in shaping attitudes towards LGBT and to examine the psychological impact of social marginalization, with a case study of the